HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA DENGAN STATUS KEBERSIHAN GIGI DAN MULUT ANAK TUNA RUNGU USIA 9-12 TAHUN DI SLB KOTA PADANG - Chindy Septia Ningsih; Didin Kustantiningtyastuti (Faculty of Dentistry Universitas Andalas, 2016)
Parents’ knowledge is very important in keeping children’s mouth and teeth clean especially on disability children. According to the researcher’s survey, it hasn’t been conducted a research yet about oral hygiene indeks of deaf children. The objective of this research is to determine the correlation of parents’ knowledge with oral hygiene indeks of 9-12 years old deaf children at extraordinary schools in Padang”. The design of this research is observational analytic with cross sectional approach. Population of this research is all deaf children at 5 extraordinary schools who are the most ages are 9-12 years old. They are 34 children whom are selected by using total sampling technique. Time of the research is in March 2016. The research instruments are questionnaire and oral hygiene status. Univariate analysis is shown in the form of frequency distribution tables and bivariate analysis is by using chi-square test with 95% α = 0.05 level of trust. Research findings showed more than a half (73,5%) children had not good level of mouth and teeth clean; only a small percentage (20,6%) parents had high knowledge; and there was no significant correlation between parents’ knowledge and oral hygiene indeks simplifield (OHI-S) of 9-12 years old deaf children at extraordinary. PValue = 0.187. Keywords : Parents’ knowledge, oral hygiene indeks of deaf children